NETosis and NADPH oxidase: at the intersection of host defense, inflammation, and injury - Almyroudis, Nikolaos; Grimm, Melissa; Davidson, Bruce; Rohm, Marc; Urban, Constantin; Segal, Brahm (Frontiers in Immunology, 2013)
Neutrophils are armed with both oxidant-dependent and –independent pathways for killing pathogens. Activation of the phagocyte NADPH oxidase constitutes an emergency response to infectious threat and results in the generation of antimicrobial reactive oxidants. In addition, NADPH oxidase activation in neutrophils is linked to activation of granular proteases and generation of neutrophil extracellular traps (NETs). NETosis involves the release of nuclear and granular components that can target extracellular pathogens. NETosis is activated during microbial threat and in certain conditions mimicking sepsis, and can result in both augmented host defense and inflammatory injury. In contrast, apoptosis, the physiological form of neutrophil death, not only leads to non-inflammatory cell death but also contributes to alleviate inflammation. Although there are significant gaps in knowledge regarding the specific contribution of NETs to host defense, we speculate that the coordinated activation of NADPH oxidase and NETosis maximizes microbial killing. Work in engineered mice and limited patient experience point to varying susceptibility of bacterial and fungal pathogens to NADPH oxidase versus NET constituents. Since reactive oxidants and NET constituents can injure host tissue, it is important that these pathways be tightly regulated. Recent work supports a role for NETosis in both acute lung injury and in autoimmunity. Knowledge gained about mechanisms that modulate NETosis may lead to novel therapeutic approaches to limit inflammation-associated injury.